KUALITAS PELAYANAN ADMINISTRASI DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN MINAHASA - Rengkuan, Raldy F; Londa, Very Y; Waleleng, Grace J (Dinamika Governance: Jurnal Ilmu Administrasi Negara, 2025)
This study aims to evaluate the quality of civil registration services at the Department of Population and Civil Registration of Minahasa Regency based on five main dimensions: reliability, responsiveness, assurance, empathy, and tangibles. The findings indicate that, in general, the services have been delivered quite well, particularly in terms of procedural reliability and staff competence. However, several issues persist, such as delays during peak hours, data entry errors, long queues, and limited use of digital technologies. The empathy dimension reflects a decent level of attentiveness to the public, although services are not yet fully inclusive for vulnerable groups. Meanwhile, the tangible aspect is considered adequate, but still requires improvements in physical facilities and the provision of more user-friendly information. To address these challenges, updates to digital administrative systems, enhanced technical and ethical training for staff, as well as infrastructure development and service quality monitoring are necessary. The study recommends the establishment of an internal service quality monitoring team as a strategic step to sustainably improve public satisfaction